Are contemporary Wars “new”? - Clara Darabont (Romanian Journal of European Affairs, 2010)
This paper will assess the existing perspectives on „new wars” in the literature. It will then analyze the degree to which contemporary wars are „new” by looking firstly at the changing nature of the state. It will not however support the view that state’s weakness is a structural cause of conflict but rather that it is a facilitator one. Finally, it will explore the degree to which globalization has impacted the role Romanian forces have to play in hotbeds such as Irak or Afghanistan. While engaging the existing literature, I argue that we must understand the „new wars” as an adapted form of engagement and not necessarily as a new breed of war.